The Effect Of Personal Learning Models On Self-Confidence And Learning Outcomes To Play Soccer In Extracurricular Men's Soccer - Rumawatine, Ztella (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aimed to determine whether the personal learning model had a significant effect on student self-confidence and the learning outcomes of students playing soccer in the men's soccer extracurricular at SMK Jeiljaka Dobo Kec. Aru Islands, Aru Islands Regency, Maluku. The method used in this study was an experiment using the One Group Pretest-Posttest Design. This design measures changes that occur in one group of research subjects before and after being given a particular treatment or intervention. The population in this study was 25 male students at SMK Jeiljaka Dobo Aru Islands. In contrast, the sample in this study was 25 people using a sampling technique, namely a saturated sample, which means that the entire population was sampled. The self-confidence instrument uses a questionnaire, while the results of learning to play used GPAI (Game Performance Assessment Instrument). Based on the processing and analysis of the data obtained, it can be seen that the significance value is 2.037, with the results of the self-confidence questionnaire testing at 2.610 and the results of learning to play results testing at 3.832. Because the significance value is more significant than 2.037, then, Ho is rejected. It can be concluded that personal models significantly affect self-confidence and student learning outcomes in playing soccer.